S100B and neuron-specific enolase levels in episodic and chronic migraine - Gonen, Murat; Ozdogan, Sevim; Balgetir, Ferhat; Demir, Caner Feyzi; Aytac, Emrah; Mungen, Bulent (Wiley, 2021)
Objectives In recent years, radiological and biochemical data have emerged regarding the development of cellular damage in the brain of patients with migraine, calling into question what has traditionally been accepted as a benign disorder. In order to investigate whether cellular damage develops in the brain of episodic migraine patient, serum levels of neuron-specific enolase (NSE) and S100B have been evaluated in recent studies. However, contradictory results were obtained in these studies. Moreover, there is no study on NSE and S100B in cases of chronic migraine. Methods Patients with episodic migraine with or without aura and chronic migraine were included. In addition, 27 healthy volunteers were included as a control group. Control group was selected from healthy volunteers of the same age and sex. We investigated serum NSE and S100B levels during the interictal period in 26 patients with episodic migraine and 27 patients with chronic migraine. Results The serum NSE and S100B levels were significantly higher in both patients with episodic and chronic migraine than controls. Although there were no significant differences in the serum NSE and S100B levels between the two patients' groups, these markers were found to be higher in cases of chronic migraine. Conclusion These results suggest that there is both neuronal and glial involvement in the two migraine groups. Elevations in these markers in cases of episodic migraine suggest that cellular damage not only results from headache episodes, but that there may be also an ongoing pathological process during the interictal period.
Keywords: chronic migraine; episodic migraine; neuron? specific enolase; S100B